Alumina-silicon carbide composite ceramic and preparation method thereof
Alumina-silicon carbide composite ceramics are prepared by compounding flaky silicon carbide with alumina and treating them with fluoride. This solves the problem of low thermal conductivity of alumina ceramics, achieves a combination of high thermal conductivity and good bending strength, reduces production costs, and is suitable for occasions such as electrostatic chucks.
Patent Information
- Application Number
- CN202410443206.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-12
- Publication Date
- 2025-10-21
AI Technical Summary
Existing alumina ceramics have low thermal conductivity, resulting in reduced performance, safety, reliability and life in high heat flux environments. In addition, aluminum nitride ceramics are complex to process and have high costs, which limits their application in fields such as electrostatic chucks.
By combining flaky silicon carbide with alumina, alumina-silicon carbide composite ceramics were prepared by constructing a thermal conduction path and optimizing the particle size distribution. The thermal conductivity was improved by combining the Hatta model, and fluoride was added to reduce the sintering temperature.
While ensuring the bending strength, the thermal conductivity of alumina ceramics is significantly improved, the production cost is reduced, and it is suitable for large-scale production.
Smart Images

Figure BDA0004789855210000091 
Figure BDA0004789855210000111
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of ceramic materials, and in particular to an aluminum oxide-silicon carbide composite ceramic and a preparation method thereof. Background Art
[0002] High-power and high-energy-density electronic devices such as 5G network base stations, electric vehicle battery systems, CPU chips, insulated-gate bipolar transistors, and electrostatic chucks face severe challenges, including the risk of fire and explosion, resulting from high heat flux, uneven temperature distribution, and localized overheating, leading to a sharp decline in performance, safety, reliability, and lifespan. These challenges necessitate superior thermal management systems to ensure the long-term safe and reliable operation of these devices. High-performance thermally conductive materials play a crucial role in these thermal management systems.
[0003] Currently, high-performance thermal conductive materials have been widely used in fields such as microelectronics and electrical technology, solar energy, aerospace, and national defense. However, achieving high thermal conductivity depends on constructing a continuous thermal conductive path or network within a high thermal resistance matrix. These thermal conductive materials contain a high content of thermal conductive particles, which will inevitably seriously damage the originally excellent electrical breakdown strength and insulation resistance. This hinders the application of these thermal conductive materials in high-voltage insulation and heat dissipation occasions such as electrostatic chucks.
[0004] At present, the thermal conductive materials used in electrostatic chucks are mainly aluminum nitride ceramics and alumina ceramics. Among them, aluminum nitride ceramics have excellent thermal conductivity (theoretical value is 320W / (m·K)), high bulk resistivity (>1013Ω·cm), and an expansion coefficient close to that of semiconductor materials (293~773K, 418x10 -6 K -1 ), but its extremely high sintering temperature (>1800°C), complex processing, and high R&D and production costs have limited its widespread use in electrostatic chucks. In contrast, alumina also possesses excellent dielectric properties, high bulk resistivity, and a suitable coefficient of expansion, providing a good foundation for its application in electrostatic chucks. However, the low thermal conductivity of alumina ceramics (~25 W / (m·K)) still limits its development.
[0005] Currently, researchers usually address the problem of low thermal conductivity of alumina in the following ways: (1) doping and modifying alumina. By doping oxides, the physical phase and morphology of the ceramic are changed, thereby regulating the overall performance of the material. However, studies have found that after doping and modifying alumina, its dielectric and mechanical properties are greatly improved, but the thermal conductivity of the ceramic is usually not significantly improved. (2) compounding alumina by introducing high thermal conductivity polymers. By constructing a thermal conductive path, the thermal conductivity of the material can be greatly improved. However, after adding high thermal conductivity polymers to alumina, although the thermal conductivity of the sample is greatly improved, the bending strength and dielectric properties of the ceramic are sacrificed.
[0006] Therefore, how to ensure that the thermal conductivity of alumina materials is improved while taking into account the bending strength has become an important task in ceramic material technology. Summary of the Invention
[0007] The present invention provides an aluminum oxide-silicon carbide composite ceramic and a preparation method thereof. The present invention uses flaky silicon carbide to composite aluminum oxide, so that the obtained composite ceramic has both good bending strength and high thermal conductivity.
[0008] According to a first aspect of the present invention, the present invention provides an aluminum oxide-silicon carbide composite ceramic, comprising aluminum oxide and flaky silicon carbide, wherein the aluminum oxide accounts for 80-97% of the total mass of the aluminum oxide-silicon carbide composite ceramic, and the flaky silicon carbide accounts for 1-20% of the total mass of the aluminum oxide-silicon carbide composite ceramic.
[0009] In the above scheme, the present invention provides an alumina-silicon carbide composite ceramic comprising alumina and flaky silicon carbide. Silicon carbide has high bending strength and high thermal conductivity. Compounding alumina with silicon carbide can effectively solve the problem of low thermal conductivity of alumina ceramics while ensuring that the composite ceramics have good bending strength. Furthermore, the present invention improves the thermal conductivity of the composite ceramic material by constructing a Hatta model. The use condition of the Hatta model is that the micromorphology of the added filler is a flaky structure. This is to more conveniently construct a heat conduction path, further construct a heat conduction network, and improve the thermal conductivity of alumina, that is, silicon carbide with a flaky microstructure is selected to further improve the thermal conductivity of the composite ceramic. Furthermore, by limiting the amount of alumina and flaky silicon carbide in the alumina-silicon carbide composite ceramic to a reasonable range, the two materials can achieve a better synergistic effect, so that the bending strength and thermal conductivity of the alumina-silicon carbide composite ceramic are more effectively improved.
[0010] In order to achieve better synergistic effect between alumina and flaky silicon carbide and make the composite ceramic material have both high bending strength and high thermal conductivity, further, the alumina accounts for 91-97% of the total mass of the alumina-silicon carbide composite ceramic, and the flaky silicon carbide accounts for 1-7% of the total mass of the alumina-silicon carbide composite ceramic.
[0011] Furthermore, the average radial dimension of the flaky silicon carbide is 0.1 μm-0.5 μm, with an aspect ratio of approximately (5-15):1. Preferably, the average radial dimension of the flaky silicon carbide is 0.4 μm, with an aspect ratio of approximately 10:1. By selecting flaky silicon carbide of appropriate size and specific surface area, the flaky silicon carbide can be more easily dispersed in alumina, which is more conducive to constructing an ideal Hatta model and thus improving the thermal conductivity of the composite ceramic material.
[0012] Specifically, the preparation method of the flaky silicon carbide may be a sol-gel method.
[0013] Furthermore, the aluminum oxide is granular aluminum oxide with a particle size D 50 It is 1 μm or less, preferably 200 nm to 1 μm, and more preferably 200 to 600 nm.
[0014] In the above scheme, the powder particle size and morphology affect the amount of organic additives used in slurry preparation, thereby affecting the slurry's rheological properties, stability, uniformity, and the quality of the green film after formation, ultimately affecting the sintering and performance of the ceramic material. Generally, smaller particles improve sintering activity and lower sintering temperatures, resulting in a denser ceramic. However, if the particles are too small, the need for organic additives increases, hindering debinding and sintering. Therefore, it is important to select an alumina matrix within an appropriate particle size range.
[0015] Furthermore, it also includes fluoride, which accounts for 1-3% of the total mass of the alumina-silicon carbide composite ceramic, preferably 2-3%; more preferably, the fluoride is selected from one or both of lithium fluoride and calcium fluoride.
[0016] In the above scheme, by adding fluoride to the alumina-silicon carbide composite ceramic, the sintering temperature of the composite ceramic material system can be reduced, the sintering density of the composite ceramic material system can be promoted, and the production cost can be reduced, so that the alumina-silicon carbide composite ceramic has high bending strength and high thermal conductivity while also having a lower sintering temperature.
[0017] Furthermore, the alumina-silicon carbide composite ceramic has a bending strength greater than 430 MPa and a thermal conductivity greater than or equal to 25 W / (m·K).
[0018] According to a second aspect of the present invention, the present invention also provides a method for preparing the above-mentioned alumina-silicon carbide composite ceramic, comprising the following steps:
[0019] Step (1): mixing aluminum oxide and flaky silicon carbide uniformly and then ball milling to obtain a mixed powder;
[0020] Step (2): uniformly mixing the obtained mixed powder with a solvent and a binder to form a slurry; casting the slurry to obtain a cast film tape;
[0021] Step (3): performing lamination hot isostatic pressing on the obtained cast film strip, and then sintering it to obtain the alumina-silicon carbide composite ceramic.
[0022] In the above scheme, the preparation method of alumina-silicon carbide composite ceramics first mixes alumina and flaky silicon carbide uniformly and then ball mills them to form a mixed powder with an ideal particle size distribution. The mixed powder is then mixed uniformly with a solvent and a binder and then tape-casted. The alumina and flaky silicon carbide are arranged in an orderly manner by tape-casting, constructing a heat conduction path. The layered arrangement of the flaky silicon carbide is then strengthened by laminated hot isostatic pressing. Finally, the alumina-silicon carbide composite ceramics with both high bending strength and high thermal conductivity are obtained by sintering. The thermal conductivity of the alumina is improved while ensuring the mechanical properties of the alumina. The alumina-silicon carbide composite ceramics of the present invention have a simple processing technology, low R&D and production costs, and are suitable for large-scale production.
[0023] In order to lower the sintering temperature of the composite ceramic, further, in step (1), alumina, flaky silicon carbide and fluoride are mixed evenly and then ball-milled to obtain a mixed powder; and in step (3), the sintering temperature is 1600-1700°C.
[0024] In order to achieve a more ideal particle size distribution after mixing alumina and flaky silicon carbide, further, in step (1), the ball milling speed is 200-300 r / min, the time is 8-12 h, and the ball-to-material ratio is (1.5-3):1;
[0025] And / or, the solvent used in ball milling is water or alcohol, and the amount thereof is 2-4 times the sum of the mass of the aluminum oxide and the flaky silicon carbide;
[0026] And / or, step (1) further comprises drying after ball milling; preferably, the drying temperature is 70-90°C.
[0027] In order to achieve a better casting effect, further, in step (2), the solvent is at least one of water, toluene, and alcohol, and the amount thereof added is 30-50% of the mass of the slurry;
[0028] And / or, in step (2), the binder is at least one of PVB, ethyl cellulose and PVA, and the amount thereof added is 5-15 wt% of the mass of the slurry;
[0029] And / or, in step (2), the thickness of the scraper used for casting is 100 μm-600 μm.
[0030] In order to achieve a better effect of strengthening the layered arrangement of the flake silicon carbide, further, in step (3), the temperature of the hot isostatic pressing is 50-85° C. and the pressure is 30-70 MPa;
[0031] And / or, in step (3), the sintering time is 1-4 hours.
[0032] Beneficial effects of the present invention:
[0033] The present invention discloses an alumina-silicon carbide composite ceramic comprising alumina and flaky silicon carbide. Silicon carbide has high bending strength and high thermal conductivity. Compounding alumina and silicon carbide can effectively solve the problem of low thermal conductivity of alumina ceramics while ensuring that the composite ceramics have good bending strength.
[0034] The preparation method of the aluminum oxide-silicon carbide composite ceramic of the present invention is simple, has low research and development and production costs, and is suitable for large-scale production. DETAILED DESCRIPTION
[0035] To make the objectives, technical solutions, and advantages of the present invention more clear, the technical solutions of the present invention are described clearly and completely below. Obviously, the embodiments described are only some of the embodiments of the present invention, not all of them. All other embodiments derived by persons of ordinary skill in the art based on the embodiments of the present invention without inventive effort are within the scope of protection of the present invention.
[0036] Example 1
[0037] This embodiment provides an aluminum oxide-silicon carbide composite ceramic, the raw material composition of which is shown in Table 1 below, and the preparation method thereof includes the following steps:
[0038] Step (1): Alumina (granular aluminum oxide, particle size D 50 The raw materials were weighed at a ratio of 95wt% (400nm) and 5wt% (0.4μm) of flaky silicon carbide (average radial dimension, approximately 10:1). The mixed powders were placed in a planetary ball mill using alcohol as the solvent at a speed of 250r / min, a ball-to-material ratio of 3:1, and a milling time of 12 hours. After ball milling, the powders were dried in an explosion-proof oven at 80°C to obtain a mixed powder.
[0039] Step (2): Place the above-mentioned mixed powder in a three-dimensional mixer and mix it evenly, then add alcohol and a binder (PVB), the weight ratio of the mixed powder to alcohol and the binder is 50:40:10, and place the obtained slurry in a casting machine, cast at 60°C, and the thickness of the scraper used for casting is 500μm to obtain a cast film tape.
[0040] Step (3): The cast film strip is laminated and hot isostatically pressed at a temperature of 75°C and a pressure of 70 MPa, and then sintered at 1750°C for 2 h to obtain an alumina-silicon carbide composite ceramic. The performance test results are shown in Table 2.
[0041] Example 2
[0042] This embodiment provides an aluminum oxide-silicon carbide composite ceramic, the raw material composition of which is shown in Table 1 below, and the preparation method thereof includes the following steps:
[0043] Step (1): Alumina (particle size D 50 The raw materials were weighed at a ratio of 97 wt% (approximately 400 nm), flaky silicon carbide (average radial dimension of 0.4 μm, aspect ratio of approximately 10:1), lithium fluoride, and calcium fluoride (calcium fluoride) in a ratio of 97 wt% (approximately 1 wt%), 1 wt% (approximately 1 wt%), and 1 wt% (approximately 1 wt%). The mixed powder was then placed in a planetary ball mill using alcohol as the solvent, at a speed of 250 rpm, a ball-to-material ratio of 3:1, and a milling time of 12 hours. After ball milling, the powder was dried in an explosion-proof oven at 80°C to obtain a mixed powder.
[0044] Step (2): Place the above-mentioned mixed powder in a three-dimensional mixer and mix it evenly, then add alcohol and a binder (PVB), the weight ratio of the mixed powder to alcohol and the binder is 50:40:10, and place the obtained slurry in a casting machine, cast at 60°C, and the thickness of the scraper used for casting is 500μm to obtain a cast film tape.
[0045] Step (3): The cast film strip is laminated and hot isostatically pressed at a temperature of 75°C and a pressure of 70 MPa, and then sintered at 1600°C for 2 h to obtain an alumina-silicon carbide composite ceramic. The performance test results are shown in Table 2.
[0046] Example 3
[0047] This embodiment provides an aluminum oxide-silicon carbide composite ceramic, the raw material composition of which is shown in Table 1 below, and the preparation method thereof includes the following steps:
[0048] Step (1): Alumina (particle size D 50The raw materials were weighed in a ratio of 95wt%:3wt%:1wt%:1wt% of calcium fluoride (calcium fluoride), 400nm of flaky silicon carbide (average radial dimension of 0.4μm, aspect ratio of approximately 10:1), and the mixed powder was placed in a planetary ball mill using alcohol as the solvent. The milling speed was 250r / min, the ball-to-material ratio was 3:1, and the milling time was 12 hours. After ball milling, the powder was dried in an explosion-proof oven at 80°C to obtain a mixed powder.
[0049] Step (2): Place the above-mentioned mixed powder in a three-dimensional mixer and mix it evenly, then add alcohol and a binder (PVB), the weight ratio of the mixed powder to alcohol and the binder is 50:40:10, and place the obtained slurry in a casting machine, cast at 60°C, and the thickness of the scraper used for casting is 500μm to obtain a cast film tape.
[0050] Step (3): The cast film strip is laminated and hot isostatically pressed at a temperature of 75°C and a pressure of 70 MPa, and then sintered at 1600°C for 2 h to obtain an alumina-silicon carbide composite ceramic. The performance test results are shown in Table 2.
[0051] Example 4
[0052] This embodiment provides an aluminum oxide-silicon carbide composite ceramic, the raw material composition of which is shown in Table 1 below, and the preparation method thereof includes the following steps:
[0053] Step (1): Alumina (particle size D 50 The raw materials were weighed in a ratio of 93wt%:5wt%:1wt%:1wt% of calcium fluoride (calcium fluoride), 400nm of flaky silicon carbide (average radial dimension of 0.4μm, aspect ratio of approximately 10:1), and the mixed powder was placed in a planetary ball mill using alcohol as the solvent. The milling speed was 250r / min, the ball-to-material ratio was 3:1, and the milling time was 12 hours. After ball milling, the powder was dried in an explosion-proof oven at 80°C to obtain a mixed powder.
[0054] Step (2): Place the above-mentioned mixed powder in a three-dimensional mixer and mix it evenly, then add alcohol and a binder (PVB), the weight ratio of the mixed powder to alcohol and the binder is 50:40:10, and place the obtained slurry in a casting machine, cast at 60°C, and the thickness of the scraper used for casting is 500μm to obtain a cast film tape.
[0055] Step (3): The cast film strip is laminated and hot isostatically pressed at a temperature of 75°C and a pressure of 70 MPa, and then sintered at 1625°C for 2 h to obtain an alumina-silicon carbide composite ceramic. The performance test results are shown in Table 2.
[0056] Example 5
[0057] This embodiment provides an aluminum oxide-silicon carbide composite ceramic, the raw material composition of which is shown in Table 1 below, and the preparation method thereof includes the following steps:
[0058] Step (1): Alumina (particle size D 50 The raw materials were weighed in a ratio of 91wt%:7wt%:1wt%:1wt% of calcium fluoride (calcium fluoride), 400nm of flaky silicon carbide (average radial dimension of 0.4μm, aspect ratio of approximately 10:1), and the mixed powder was placed in a planetary ball mill using alcohol as the solvent. The milling speed was 250r / min, the ball-to-material ratio was 3:1, and the milling time was 12 hours. After ball milling, the powder was dried in an explosion-proof oven at 80°C to obtain a mixed powder.
[0059] Step (2): Place the above-mentioned mixed powder in a three-dimensional mixer and mix it evenly, then add alcohol and a binder (PVB), the weight ratio of the mixed powder to alcohol and the binder is 50:40:10, and place the obtained slurry in a casting machine, cast at 60°C, and the thickness of the scraper used for casting is 500μm to obtain a cast film tape.
[0060] Step (3): The cast film strip is laminated and hot isostatically pressed at a temperature of 75°C and a pressure of 70 MPa, and then sintered at 1625°C for 2 h to obtain an alumina-silicon carbide composite ceramic. The performance test results are shown in Table 2.
[0061] Examples 6-10
[0062] This embodiment provides an aluminum oxide-silicon carbide composite ceramic, which is different from the first embodiment in that the raw material composition of the aluminum oxide-silicon carbide composite ceramic is different.
[0063] The difference between the preparation method and Example 1 is that in step (3), the sintering temperature is different, and the specific differences are shown in Table 1 below.
[0064] Comparative Example 1-2
[0065] This comparative example provides an aluminum oxide-silicon carbide composite ceramic, which is different from Example 1 in that the raw material composition of the aluminum oxide-silicon carbide composite ceramic is different.
[0066] The difference between the preparation method and Example 1 is that in step (3), the sintering temperature is different, and the specific differences are shown in Table 1 below.
[0067] Table 1
[0068]
[0069] Comparative Example 3
[0070] This comparative example provides an alumina-silicon carbide composite ceramic, which is different from Example 1 in that granular silicon carbide is used instead of flake silicon carbide, and the particle size of the granular silicon carbide is 1 μm.
[0071] The difference between the preparation method and Example 1 is that in step (3), the sintering temperature is different, and the specific sintering densification temperature is 1700°C.
[0072] Comparative Example 4
[0073] This comparative example provides an alumina-flaky alumina composite ceramic, which differs from Example 1 in that flaky alumina is used instead of flaky silicon carbide, and the radial dimension of the flaky alumina is 11.3 μm and the thickness is 1.3 μm.
[0074] The difference between the preparation method and Example 1 is that in step (3), the sintering temperature is different, and the specific sintering densification temperature is 1650°C.
[0075] The alumina-silicon carbide composite ceramics of Examples 1-10 and Comparative Examples 1-4 were subjected to bending strength tests and thermal conductivity tests. The bending strength test method was a three-point bending strength test method, and the thermal conductivity test method was a laser flash method. The test results are shown in Table 2 below.
[0076] Table 2 Performance of alumina-silicon carbide composite ceramics of Examples and Comparative Examples
[0077] Sample number Bending strength / Mpa Measuring temperature / ℃ <![CDATA[Thermal conductivity / W·m -1 ·K -1 > Example 1 463 200 40.2 Example 2 453 200 28.3 Example 3 460 200 35.1 Example 4 453 200 40.2 Example 5 435 200 33.8 Example 6 400 200 28.1 Example 7 452 200 38.8 Example 8 453 200 38.3 Example 9 448 200 40 Example 10 440 200 37.3 Comparative Example 1 450 200 25 Comparative Example 2 331 200 12.1 Comparative Example 3 420 200 35.5 Comparative Example 4 477 200 15.7
[0078] As shown in Table 2, the addition of flake silicon carbide causes the thermal conductivity of the alumina-silicon carbide composite ceramic material to increase first and then decrease, and the maximum value (40.2 W·m -1 ·K -1 ), which is 0.6 times higher than that of pure alumina ceramics. This is because the sheet-like silicon carbide forms an effective heat conduction path in the composite material system after tape casting, which is suitable for the thermal conductivity calculation method of the Hatta model:
[0079]
[0080] Where K 复 is the thermal conductivity of the composite material, λ1 is the thermal conductivity of the matrix, and λ2 is the thermal conductivity of the flake filler. S is the orientation factor, whose value depends on the direction of the thermal conductivity measurement: in the in-plane direction, S = πL / 4X; in the out-of-plane direction, S = 1-πL / 2X, where L and X are the diameter and thickness of the flake filler, respectively. V2 is the volume fraction of the flake filler in the composite system. The measurement direction used in this invention is out-of-plane orientation. Calculations show that the measured values for the experimental samples are generally consistent with the theoretical values.
[0081] In addition, the alumina-silicon carbide composite ceramic of the present invention improves thermal conductivity while taking into account its mechanical properties. After adding flake SiC, the bending strength of the sample increases slightly and then decreases. This phenomenon is due to the fact that the thermal expansion coefficient of SiC (3.7*10 -6 ) and the thermal expansion coefficient of Al2O3 (7.3*10 -6 ), so when the content of flake SiC continues to increase, the material properties deteriorate due to the appearance of pores near the interface between the two.
[0082] The examples show that adding fluoride to an alumina ceramic system can effectively reduce the overall sintering temperature and improve the overall performance of the material. When the flaky SiC content in the system is 5wt%, the sample achieves peak thermal conductivity while maintaining flexural strength, thus achieving the best overall performance in Example 4.
[0083] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the various embodiments of the present invention.
Claims
1. An alumina-silicon carbide composite ceramic, characterized in that: The aluminum oxide and flaky silicon carbide composite ceramics comprise aluminum oxide and flaky silicon carbide, wherein the aluminum oxide accounts for 80-97% of the total mass of the aluminum oxide-silicon carbide composite ceramics, and the flaky silicon carbide accounts for 1-20% of the total mass of the aluminum oxide-silicon carbide composite ceramics.
2. The alumina-silicon carbide composite ceramic according to claim 1, characterized in that: The aluminum oxide accounts for 91-97% of the total mass of the aluminum oxide-silicon carbide composite ceramic, and the flaky silicon carbide accounts for 1-7% of the total mass of the aluminum oxide-silicon carbide composite ceramic.
3. The alumina-silicon carbide composite ceramic according to claim 1 or 2, characterized in that: The average radial size of the flaky silicon carbide is 0.1 μm-0.5 μm, and the aspect ratio is about (5-15):1; preferably, the average radial size of the flaky silicon carbide is 0.4 μm, and the aspect ratio is about 10:
1.
4. The alumina-silicon carbide composite ceramic according to any one of claims 1 to 3, characterized in that: The aluminum oxide is granular aluminum oxide, and its particle size D 50 It is 1 μm or less, preferably 200-600 nm.
5. The alumina-silicon carbide composite ceramic according to any one of claims 1 to 4, characterized in that: It also includes fluoride, which accounts for 1-3% of the total mass of the alumina-silicon carbide composite ceramic, preferably 2-3%; more preferably, the fluoride is selected from one or both of lithium fluoride and calcium fluoride.
6. The alumina-silicon carbide composite ceramic according to any one of claims 1 to 5, characterized in that: The alumina-silicon carbide composite ceramic has a bending strength greater than 430 MPa and a thermal conductivity greater than or equal to 25 W / (m·K).
7. The method for preparing the alumina-silicon carbide composite ceramic according to any one of claims 1 to 6, characterized in that: The steps include: Step (1): mixing aluminum oxide and flaky silicon carbide uniformly and then ball milling to obtain a mixed powder; Step (2): uniformly mixing the obtained mixed powder with a solvent and a binder to form a slurry; casting the slurry to obtain a cast film tape; Step (3): The obtained cast film strip is laminated and hot isostatically pressed, and then sintered to obtain the alumina-silicon carbide composite ceramic.
8. The preparation method according to claim 7, characterized in that In step (1), aluminum oxide, flaky silicon carbide and fluoride are uniformly mixed and then ball-milled to obtain a mixed powder; in step (3), the sintering temperature is 1600-1700°C.
9. The preparation method according to claim 7, characterized in that In step (1), the ball milling speed is 200-300 r / min, the time is 8-12 h, and the ball-to-material ratio is (1.5-3):1; And / or, the solvent used in ball milling is water or alcohol, and the amount thereof is 2-4 times the sum of the mass of the aluminum oxide and the flaky silicon carbide; And / or, step (1) further comprises drying after ball milling; preferably, the drying temperature is 70-90°C.
10. The preparation method according to claim 7, characterized in that In step (2), the solvent is at least one of water, toluene, and alcohol, and the amount of the solvent added is 30-50% of the mass of the slurry; And / or, in step (2), the binder is at least one of PVB, ethyl cellulose and PVA, and the amount thereof added is 5-15 wt% of the mass of the slurry; And / or, in step (2), the thickness of the scraper used for casting is 100 μm-600 μm; And / or, in step (3), the temperature of the hot isostatic pressing is 50-85°C and the pressure is 30-70 MPa; And / or, in step (3), the sintering time is 1-4 hours.